Rare findings of capsule endoscopy. Clinical observation - I. V. Makarov; A. Yu. Sidorov; A. V. Zhdanov; V. E. Zaytsev; D. A. Korolev; V. Ya. Shibanov; A. D. Blashentseva; R. M. Romanov; E. A. Khaliullina (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
The article provides a brief overview of the frequency, prevalence of use, and results of video capsule endoscopy in patients with various indications after undergoing CT/MRI enterography or barium sulfate enterography. A clinical case is presented where a patient with symptoms of gastrointestinal bleeding underwent video capsule endoscopy, revealing a small bowel tumor, followed by surgical treatment. This non-invasive technique enables obtaining more accurate data for decision-making regarding further treatment strategies.